A expansão dos cursos de graduação em serviço social no Nordeste brasileiro em tempo de capitalismo neoliberal - Almeida, Andréa Carla Pereira dos Santos (2013)
This dissertation research object is the analysis of the expansion of undergraduate courses in Social Work in northeastern Brazil in times of neoliberal capitalism. With this, the objective was to understand and analyze the public policy of higher education and its effects on the expansion of courses in Social Work in northeastern Brazil and the neoliberal context. Specifically , we sought to identify in the National Higher Education aspects that contributed to the development of higher education in Brazil, and particularly in the Northeast region of the country; reflect on the wide university reform triggered by Lula´s government (2003-2010 ) in the mold of neoliberal capitalism and its influence on the increase of Institutions of Higher Education; analyze the data issued by official bodies responsible for disseminating information on Higher Education in Brazil and the course of Social Service in this country, particularly in the Northeast. This is an exploratory research outlined by literature and documents. Among the results can be noted that , in fact, was the expansion of higher education in Brazil as a whole, especially in Social Work courses both in classroom mode as the distance, in the Northeast . In 2001, Brazil had 183 public HEIs while in the same period, the number of private institutions was 1208. In 2012, the ratio was 284 to 2081 IES public private IES. In the period 2000-2012, the number of courses in Social Work authorized by the Ministry of Education, through the Federal Education Council, to operate nationwide increased from 88 to 694. In the Northeast, for this same period, the number of undergraduate courses in Social Work went from 14 to 170. Of this total, 89 courses work in classroom mode and 81 in distance mode.